2004
DOI: 10.1007/s00466-004-0570-4
|View full text |Cite
|
Sign up to set email alerts
|

A Petrov?Galerkin finite element scheme for the regularized long wave equation

Abstract: A Petrov-Galerkin finite element method (FEM) for the regularized long wave (RLW) equation is proposed. Finite elements are used in both the space and the time domains. Dispersion correction and a highly selective dissipation mechanism are introduced through additional streamline upwind terms in the weight functions. An implicit, conditionally stable, one-step predictor-corrector time integration scheme results. The accuracy and stability are investigated by means of local expansion by Taylor series and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…. , we need to determine the N + 1 unknown coefficients λ n j from boundary conditions (5) given at x 0 and x N and collocating U n at the remaining N − 1 distinct uniformly distributed interior points…”
Section: The Rbf Collocation Methodsmentioning
confidence: 99%
“…. , we need to determine the N + 1 unknown coefficients λ n j from boundary conditions (5) given at x 0 and x N and collocating U n at the remaining N − 1 distinct uniformly distributed interior points…”
Section: The Rbf Collocation Methodsmentioning
confidence: 99%
“…Nevertheless, in an earlier work [43] the authors showed that a similar scheme for the RLW equation would display the same leading error terms for both the second and the third corrector steps. The RLW model is the Boussinesq model counterpart for kinematic waves, and therefore one might expect that a similar behaviour will be found within the framework of the latter model.…”
Section: Predictor-correctormentioning
confidence: 88%
“…Space integration of the equation is achieved with the quartic B-splines by substituting the nodal values U and their derivatives U x , U xx in Eqs. (12) and (13). This yields the following coupled matrix system of the first-order ordinary differential equations:…”
Section: Quartic B-spline Collocation Methods II (Qbcm2)mentioning
confidence: 99%
“…The change in water level of magnitude U(x, 0) is centered on x = x c . To make comparisons with earlier studies [8,13,18,19,22,24], the parameters are taken as ε = 1.5, µ = 0.16666667, U 0 = 0.1, x c = 0, a = −36, b = 300, mesh size h = 0.24, and time step t = 0.1, d = 2, 5. Figures 20 and 21 show the developments of the undular bores at time t = 250.…”
Section: Wave Undulationmentioning
confidence: 99%